Urbanization and Housing Investment - Dasgupta, Basab; Lall, Somik V.; Lozano-Gracia, Nancy (World Bank Group, Washington, DC, 2014)
This paper provides the first systematic empirical assessment of the pace at which housing investment has responded to rising demand from urbanization. The assessment used National Accounts Statistics to build a data set of residential housing investment for more than 90 countries. The data set explicitly accounts for investment by households, the government, and the private sector. The analysis finds that housing investment follows an S-shaped trajectory taking off around per capita GDP of about $3,000 (US$2005) and tapering down at per capita GDP around $36,000 (US$2005). The analysis also finds that between 2001 and 2011, housing investment in low-income economies averaged 4.56 percent of gross domestic product and 9.12 percent in upper-middle-income economies. An important finding is that countries in Sub-Saharan Africa have housing elasticities similar to comparable low-income and lower-middle-income economies. In financing housing investment, the paper finds that developing countries tend to rely much more on domestic savings and government debt, whereas high-income Organisation for Economic Co-operation and Development countries lever capital markets by tapping foreign savings. Not only does excessive reliance on domestic savings and government debt increase the sensitivity of housing investment to the cyclicality of growth of gross domestic product, it also can potentially crowd out investments in health and education.